Telaah Tematik dan Kontekstual Terhadap Hadis-hadis tentang Interaksi Islam dan Yahudi - Muhammad Tasrif (AL-TAHRIR, 2011)
In the era of globalization—characterized by a rapid flow of information, people, and goods with no limits—the issue of multiculturalism has been to be a challenge to Muslims. Intercultural meeting is something unavoidable. In this respect, the issue of the relation of Islam and Judaism is to be a crucial one. Among Muslims, the relationship has been colored by negative perception especially if it is justified by the verses of the Koran and the hadith of the Prophet. Hizbut Tahrir Indonesia (HTI) is among the Muslim groups that have a negative perception of the relationship. This study examines the traditions of the Prophet pertaining the relationship of Muslims and Jews thematically and contextually, especially the social construction of HTI Ponorogo on these traditions. Thematic and contextual study of the traditions of the relationship of Muslims and Jews shows that the Prophet’s attitude toward Jews, or vice versa, varies from negative to positive, appreciative. This evidence suggests that such attitude, especially negative one, is not a permanent attitude. Instead, these attitudes had been temporarily and conditionally formed. Thus, based on the traditions of the Prophet, a negative permanent attitude toward Jews is not theologically justified. Meanwhile, the examination of the social construction of Ponorogo branch of Hizbut Tahrir Indonesia shows various theological types: rigid-textualist and soft-textualist. The first group see the hadiths of the relation of Islam and Judaism as a source of Sharia which should be implemented in a fixed manner. The second group have the attitude that is consistent with the first group, by giving a space for a potential change of the teaching due to the changes of circumstances.